Therapy of porphyria with oral activated charcoal - Hift, R J (UCT/MRC Liver Centre, 2024)
The porphyrias are a group of disorders of the haem biosynthetic pathway. Each is ascribed to a unique deficiency of an enzyme of this pathway. Figure 1.1 shows this pathway and the position of the affected enzyme in each form of porphyria. PORPHYRINOGENS AND PORPHYRINS The porphyrinogens are cyclic tetrapyrroles in which the macrocycle exists in the unconjugated state, the four pyyrole rings being connected by single-bonded methylene bridges. Four pyrrole rings are connected by single bonds. The corresponding conjugated forms are known as the porphyrins, in which the rings are connected by double-bonded methene bridges). The conversion occurs spontaneously in the presence of oxygen, light acid or other oxidising conditions, and is accompanied by a conformational change. Where the porphyrinogens are flexible, non-aromatic compounds, the porphyrins are highly aromatic, rigid, planar macrocycles and are inherently more stable than most porphyrinogens. With one exception, f ellochelatase, which acts upon protoporphyrin, the enzymes of the pathway can use only the porphyrinogens as substrates. Yet most diagnostic and research work in the laboratory is performed on the corresponding porphyrins. This is not only because of the difficulty of maintaining porphyrinogens in the reduced state, but also because the double-bonded structure of the porphyrins confers the property of fluorescence on them, which provides a suitable method . for their detection and quantitation. This is discussed further in the chapters which follow. The relative proportions in which the porphyrins and porphyrinogens exist in tissues ( and indeed in urine, stool and plasma) are largely unknown, though one might expect a considerable proportion to be present as the porphyrin, in view of the rapidity with which porphyrinogens will oxidise.